A Diachronic Approach to Criteria of Existence in Empirical Sciences - Raźniak, Maciej (Roczniki Filozoficzne, 2025)
The aim of this paper is to propose a new approach to criteria of existence in natural sciences which can be called a diachronic one. In these considerations, we start with a general analysis of criteria of existence and discuss two competing views on this issue: first, the strategy put forward by logical empiricists that emphasizes the importance of empirical criteria of existence and, second, the view presented by Willard Van Orman Quine, who claimed that the only way to accept the existence of certain objects is to apply the theoretical criterion (ontological commitments criterion). Our main idea is to develop an approach to applying criteria so that strategies proposed by Quine and logical empiricists (so-called synchronic models) do not antagonize each other, but also can be considered adequate in some circumstances.